2020
DOI: 10.1016/j.gpb.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA Binding Proteome of Proliferating and Differentiated Muscle Cells

Abstract: Muscle formation is a coordinated process driven by extensive gene expression changes where single cells fuse together to form multinucleated muscle fibers. Newly synthesized mRNAs are then regulated by RNA binding proteins (RBPs), affecting post-transcriptional transcript metabolism. Here, we determined how large-scale gene expression changes affect the catalog of RBPs by studying proliferating and differentiated muscle cells in healthy and dystrophic conditions. Transcriptomic analysis showed that the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Consistent with the considerations above, we observed that several classical core RBPs (splicing factors, ribosomal proteins, and hnRNPs) show decreased binding in four comparative RIC studies employing different perturbations in distinct mammalian cell lines ( Figure 2 ; Milek et al, 2017 ; Perez-Perri et al, 2018 ; Garcia-Moreno et al, 2019 ; Hiller et al, 2020 ). Conversely, proteins with moonlighting RNA-binding activity such as metabolic enzymes tend to show increased binding.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with the considerations above, we observed that several classical core RBPs (splicing factors, ribosomal proteins, and hnRNPs) show decreased binding in four comparative RIC studies employing different perturbations in distinct mammalian cell lines ( Figure 2 ; Milek et al, 2017 ; Perez-Perri et al, 2018 ; Garcia-Moreno et al, 2019 ; Hiller et al, 2020 ). Conversely, proteins with moonlighting RNA-binding activity such as metabolic enzymes tend to show increased binding.…”
Section: Introductionsupporting
confidence: 87%
“…Quantitative interpretation of CLIP-like experiments is difficult ( Ramanathan et al, 2019 ), and only performed in exceptional cases ( Schueler et al, 2014 ) or indirectly ( Gregersen et al, 2014 ; Milek et al, 2017 ; Smith et al, 2021 ). In contrast, RIC-like experiments are often used to assess changes in RNA-binding for RBPs across conditions ( Hentze et al, 2018 ), and several groups have identified context-specific regulatory RBPs in mammalian tissue culture cells ( Boucas et al, 2015 ; Liepelt et al, 2016 ; Milek et al, 2017 ; Perez-Perri et al, 2018 ; Garcia-Moreno et al, 2019 ; Ignarski et al, 2019 ; Queiroz et al, 2019 ; Trendel et al, 2019 ; Hiller et al, 2020 ; Smith et al, 2021 ), zebrafish and fly embryos ( Sysoev et al, 2016 ; Despic et al, 2017 ), yeast ( Shchepachev et al, 2019 ; Bresson et al, 2020 ), and plant cells ( Marondedze et al, 2019 ). While it is tempting to interpret differences in RIC-like experiments as changes in RBP-RNA interaction (RNA-bound protein fraction), this is not to be taken for granted.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, post-transcriptional regulation of gene expression orchestrated by RBPs but also other factors, such as non-coding RNAs and even MRFs ( Panda et al, 2016 ; Luo et al, 2021 ), plays crucial roles in muscle development and regeneration. Many RBPs are differentially associated with target mRNAs in proliferating myoblasts or differentiated myotubes to regulate distinct aspects of RNA metabolism in a stage-dependent manner ( Hiller et al, 2020 ). As will be discussed below, this is often correlated with their dynamic expression and subcellular localization during myogenesis.…”
Section: An Overview Of Post-transcriptional Regulation In Muscle Developmentmentioning
confidence: 99%
“…Transcriptome and proteome studies have not only identified hundreds of muscle-specific RBPs but also revealed changes in the interactome during muscle differentiation ( Hiller et al, 2020 ). With so many RBPs dynamically implicated in different steps of myogenesis and in multiple aspects of post-transcriptional regulation of gene expression, it is not surprising that they functionally interact in a tight network to coordinate muscle development and maintain muscle homeostasis.…”
Section: Functional Interactions Between Rna-binding Proteins Coordinate Gene Expression During Myogenesismentioning
confidence: 99%
“…CLIP and RIC have provided us with useful catalogs of RBPs and their RNA-binding sites (Gerstberger, Hafner and Tuschl, 2014; Maatz et al ., 2014; Hentze et al ., 2018; Zhu et al ., 2019; Van Nostrand et al ., 2020). Also, comparative RIC studies provided information about how the interaction of RBPs with RNA changes upon perturbation (Milek et al ., 2017; Perez-Perri et al ., 2018; Garcia-Moreno et al ., 2019; Hiller et al ., 2020). However, the impact of PTMs in RBPs on their interaction with RNAs has not yet been investigated systematically.…”
Section: Introductionmentioning
confidence: 99%